The role of Nrf2 in periodontal disease by regulating lipid peroxidation, inflammation and apoptosis - Ma, Fengyu; Luo, Shangdie; Lu, Chunting; Jiang, Xinrong; Chen, Kexiao; Deng, Jianwen; Ma, Shuyuan; Li, Zejian (Frontiers in Endocrinology, 2022)
Nuclear factor E2-related factor 2(Nrf2) is a transcription factor that mainly regulates oxidative stress in the body. It initiates the expression of several downstream antioxidants, anti-inflammatory proteins and detoxification enzymes through the Kelch-like ECH-associating protein 1 (Keap1) -nuclear factor E2-related factor 2(Nrf2) -antioxidant response element (ARE) signaling pathway. Its anti-apoptosis, anti-oxidative stress and anti-inflammatory effects have gradually become the focus of periodontal disease research in recent years. In this paper, the structure and function of Nrf2 pathway and its mechanism of action in the treatment of periodontitis in recent years were analyzed and summarized, so as to further clarify the relationship between Nrf2 pathway and oxidative stress in the occurrence and development of periodontitis, and to provide ideas for the development of new treatment drugs targeting Nrf2 pathway.